Long-term course of children who underwent the laparoscopic Collis-Nissen procedure. Preliminary communication - Carlos García-Hernández; Lourdes Carvajal-Figueroa; Christian Archivaldo-García; Sergio Landa-Juarez (Elsevier, 2023)
Introduction: Short esophagus is the inability to obtain an adequate abdominal esophageal portion during anti-reflux surgery.  An alternative treatment is the Collis type esophagogastroplasty. This minimally invasive procedure has been performed on children, but it is not known what happens in the long term. The objective is to know the long-term evolution in children who underwent the minimally invasive Collis-Nissen procedure. Material and methods: An IRB exempt prospective, observational study of a case series of patients with short esophagus who underwent a laparoscopic Collis-Nissen procedure more than 5 years after surgery. All of them underwent a contrasted study and endoscopy with biopsy 5 years after the surgery. Results: The study included 8 children 5 years after having surgery. Mostly asymptomatic. The esophagogastroduodenal series showed the same caliber in the native esophagus as in the gastroplasty with adequate clearance and functional fundoplication.  Endoscopy showed growth of the gastroplasty, continent cardia and an efficient fundoplication. Histopathologic study of the gastroplasty showed chronic nonspecific inflammation with pseudostratified mucin-producing columnar pseudostratified epithelium with adequate maturation. Discussion: The Collis-Nissen procedure in children using the cardia area and the proximal part of the lesser curvature is useful in the long-term control of reflux disease, preserving an adequate portion of the abdominal esophagus without peptic complications. Level of evidence: II